Preliminary characterization of microplastics in beef hamburgers - E. Visentin; G. Niero; F. Benetti; A. Perini; M. Zanella; M. Pozza; M. De Marchi (Meat Science, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Surface facet Fe2O3-based visible light photocatalytic activation of persulfate for the removal of RR120 dye: nonlinear modeling and optimization - Saad U. Khan; Hammad Khan; Sajjad Hussain; Lilian D. M. Torquato; Sabir Khan; Raul G. Miranda; Danielle P. Oliveira; Daniel J. Dorta; João A. Lima Perini; Hyeok Choi; Maria V. Boldrin Zanoni (Environmental Science and Pollution Research, 2022)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Sequencing of Tuta absoluta genome to develop SNP genotyping assays for species identification - Christine A. Tabuloc; Kyle M. Lewald; William R. Conner; Yoosook Lee; Ernest K. Lee; Alexander B. Cain; Kristine E. Godfrey; Judit Arnó; Nuria Agustí; Clerison R. Perini; Jerson C. Guedes; Frank G. Zalom; et al. (Journal of Pest Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Phylogeography Approach of Diloboderus abderus (Coleoptera: Melolonthidae) in the Southern Cone of America - I Valmorbida; J A Arnemann; M A Cherman; C B Bevilacqua; C R Perini; G A Ugalde; J V C Guedes (Neotropical Entomology, 2019)

Current knowledge of Umbrian macrofungi (central Italy) - P. Angelini; A. Arcangeli; G. Bistocchi; A. Rubini; R. Venanzoni; C. Perini (Plant Biosystems, 2017)

Spatial scale mediates the effects of biodiversity on marine primary producers - Matthew E. S. Bracken; James G. Douglass; Valerie Perini; Geoffrey C. Trussell (Ecology, 2017)
Most studies evaluating the effects of biodiversity on ecosystem functioning are conducted at a single location, limiting our understanding of how diversity–function relationships may change when measured across different spatial scales. We conducted a species‐removal experiment at three sites nested in each of three regions along the rocky intertidal coastline of the Gulf of Maine, USA , to evaluate the potential for scale‐dependent effects of species loss on the biomass of intertidal seaweed assemblages. We randomly assigned 50 plots in the mid‐intertidal zone at each site to one of five treatments ( n = 10 plots each): an unmanipulated control, a polyculture plot that contained our three target seaweed species, and three monoculture plots. We manipulated diversity by removing all non‐target species from monoculture and polyculture plots, then removing additional biomass from polyculture plots, proportionate to species' relative abundances, so that the average amount removed from monoculture and polyculture plots was equivalent at each site. At the largest spatial scale, all sites considered together, after accounting for region and site nested within region seaweed diversity had consistent, positive effects on seaweed cover. Diverse polyculture plots always had higher cover than was predicted by the average performance of the component seaweed species and usually had higher cover than even the best‐performing component species. Diversity effects weakened and became less consistent at smaller spatial scales, so that at the scale of individual sites, diverse polycultures only performed better than the average of monocultures ~40% of the time. Hence, our results indicate that weak and/or inconsistent biodiversity effects at the level of individual sites may scale up to stronger, more consistent effects at larger spatial scales. Quantitative summaries of biodiversity experiments conducted at the scale of individual sites do not capture this spatial aspect of biodiversity effects and may therefore underestimate the functional consequences of biodiversity loss.

Assessment of ectomycorrhizal fungal communities in the natural habitats of Tuber magnatum (Ascomycota, Pezizales) - M. Leonardi; M. Iotti; M. Oddis; G. Lalli; G. Pacioni; P. Leonardi; S. Maccherini; C. Perini; E. Salerni; A. Zambonelli (Mycorrhiza, 2013)

Wild and cultivated mushrooms as a model of sustainable development - D. Donnini; M. L. Gargano; C. Perini; E. Savino; C. Murat; S. Di Piazza; E. Altobelli; E. Salerni; A. Rubini; G. L. Rana; M. Bencivenga; R. Venanzoni; et al. (Plant Biosystems, 2013)

Interactions of fungi with other organisms - S. Perotto; P. Angelini; V. Bianciotto; P. Bonfante; M. Girlanda; T. Kull; A. Mello; L. Pecoraro; C. Perini; A. M. Persiani; A. Saitta; S. Sarrocco; et al. (Plant Biosystems, 2013)

Fungal biodiversity and in situ conservation in Italy - G. Venturella; E. Altobelli; A. Bernicchia; S. Di Piazza; D. Donnini; M. L. Gargano; S. P. Gorjòn; V. M. Granito; A. Lantieri; D. Lunghini; A. Montemartini; F. Padovan; et al. (Plant Biosystems, 2011)

Non-invasive assessment of tumor neovasculature: techniques and clinical applications - Rodolfo Perini; Regine Choe; Arjun G. Yodh; Chandra Sehgal; Chaitanya R. Divgi; Mark A. Rosen (Cancer and Metastasis Reviews, 2008)

Chemical and isotopic (C, O, Sr, Nd) characteristics of the Xiluvo carbonatite (central-western Mozambique) - P. Censi; G. Perini; L. Vasconcelos; V. Morra; F. Guerreiro; L. Bennio; L. Melluso (Mineralogy and Petrology, 2004)

Crystallization conditions of leucite-bearing magmas and their implications on the magmatological evolution of ultrapotassic magmas: the Vico Volcano, Central Italy - G. Perini; S. Conticelli (Mineralogy and Petrology, 2002)